(untitled) (Sustainability in Debate, 2016)
Reinette Biggs, Maja Schlüter, Michael L. Schoon (editores). Principles for Building Resistance: Sustaining Ecosystem Services in Social-Ecological Systems. Cambridge University Press, 2015. 290 p. ISBN: 978-1-107-08265-6.